PENGARUH APLIKASI CAKE DALAM MENINGKATKAN KEMAMPUAN BAHASA INGGRIS MAHASISWA PGSD - Junaidi Junaidi; Alya Aulia Faiza (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2025)
In this era we can learn English through various media such as YouTube, games, applications, etc. However, in reality, there are many students who cannot speak English fluently. The aims of this study were (1) to find out the effectiveness of cake application in improving students' English skills, (2) to describe the obstacles students experience in learning English. Data collection techniques include interviews, observation, literature studies, reading tests. The results of the study were (1) students' English skills increased after learning through the "cake" application, (2) The obstacles experienced by students in learning English were the embarrassment of using English when they had not mastered it and had a little vocabulary.